2022
DOI: 10.1097/mca.0000000000001141
|View full text |Cite
|
Sign up to set email alerts
|

Premature acute coronary syndrome: understanding the early onset

Abstract: Introduction Acute coronary syndrome (ACS) is less frequent in young adults, but it has become a significant health problem, associated with the increasing prevalence of modifiable risk factors.Objectives To characterize patients admitted with premature ACS, comparing with those with nonpremature ACS. MethodsWe performed a retrospective study encompassing patients of the Portuguese Registry (ProACS), comparing two groups: one composed of men less than 55 and women less than 65 years old; and other with men ≥55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In terms of interventional characteristics, the left anterior descending artery was the most commonly involved vessel, confirming the findings of other studies. 6,24) Furthermore, a comparison of the number of diseased vessels showed that the premature ACS group had a significantly higher incidence of single-vessel lesions and a lower incidence of triple-vessel lesions than the nonpremature ACS group, which is similar to previous findings. 7,10,25) Because patients with nonpremature ACS were older, these results indicated that a high incidence of multivessel lesions may be associated with aging.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In terms of interventional characteristics, the left anterior descending artery was the most commonly involved vessel, confirming the findings of other studies. 6,24) Furthermore, a comparison of the number of diseased vessels showed that the premature ACS group had a significantly higher incidence of single-vessel lesions and a lower incidence of triple-vessel lesions than the nonpremature ACS group, which is similar to previous findings. 7,10,25) Because patients with nonpremature ACS were older, these results indicated that a high incidence of multivessel lesions may be associated with aging.…”
Section: Discussionsupporting
confidence: 88%
“…Most patients in our study experienced NSTE-ACS, which was inconsistent with the trends in the majority of published studies. 6,25,27) This indicated that the majority of ACS types in patients in this region of China between July 2009 and August 2011 were NSTE-ACS, constituting a potential bias attributed to the use of singlecenter data. It is known that NSTE-ACS is more associated with multivessel disease, suggesting that patients with NSTE-ACS have worse clinical outcomes, 28 such as greater late mortality and an increased reinfarction risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations